Business management training for MSMEs GRD Frozen Food - Farida Farida; Fatma Irmaliya; Yuli Ade Hapsari; Ninda Arumsari; Danang Sarif Hidayatullah; Maesaroh Maesaroh (Community Empowerment, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in increasing people's income in Junjungan Hamlet. One of them is the MSME GRD Frozen Food, which is able to employ a large number of people from the surrounding area. However, because these MSMEs haven't marketed digitally and haven't kept track of their finances, their business management isn't ideal. The purpose of this program is to implement social media marketing and simple bookkeeping using Excel. Socialization, training, and continuous assistance with marketing and accounting books are all used to achieve these objectives. The results of the activity show that the MSMEs of GRD Frozen Food are capable of using Instagram for marketing and of compiling simple bookkeeping, both manually and electronically.